Concordance between microsatellite instability and mismatch repair protein expression in colorectal cancer and their clinicopathological characteristics: a retrospective analysis of 502 cases - Ye, Meihua; Ru, Guoqing; Yuan, Hang; Qian, Lili; He, Xianglei; Li, Shuangshuang (Frontiers in Oncology, 2023)
Microsatellite instability (MSI) is one of the hallmarks of colorectal cancer (CRC). Mismatch repair (MMR) protein expression may reflect MSI status. To analyze the concordance between MSI and MMR expression in CRC and their clinicopathological characteristics, 502 CRC patients were retrospectively collected in this study. Polymerase chain reaction-capillary electrophoresis (PCR-CE) was used to measure MSI, and MMR expression was determined by immunohistochemistry (IHC). The causes of non-concordance were analyzed. Chi-square test was used to find the correlation between MSI and various clinicopathological parameters. PCR-CE results showed 64 (12.7%) patients had high microsatellite instability (MSI-H); low microsatellite instability (MSI-L) and microsatellite stable (MSS) cases were 19 (3.8%)and 419 (83.5%), respectively. With regard to IHC, 430 (85.7%) showed proficient mismatch repair (pMMR) and 72 (14.3%) showed deficient mismatch repair (dMMR). The coincidence rate of MSI and MMR expression in CRC was 98.4% (494/502), with good concordance (Kappa = 0.932). Using PCR-CE as the gold standard, the sensitivity, specificity, positive predictive value, and negative predictive value of IHC were 100%, 98.2%, 88.9%, and 100%, respectively. MSI-H was more common in women, right colon, tumors ≥ 5 cm, ulcerative type, mucinous adenocarcinoma, poor differentiation, T stage I/II, and without lymph node or distant metastasis for CRC patients. In summary, MSI exhibited some typical clinicopathological characteristics. MSI and MMR expression in CRC had good concordance. However, it is still extremely necessary to perform PCR-CE. We recommend that testing packages of different sizes should be developed in clinical practice to create a testing echelon, to facilitate comprehensive selection according to experimental conditions, clinical diagnosis, and treatment needs